The gut microbiome, immune modulation, and cognitive decline: insights on the gut-brain axis - Zhang, Ruyi; Ding, Ning; Feng, Xicui; Liao, Wenli (Frontiers in Immunology, 2025)
The gut microbiome has emerged as a pivotal area of research due to its significant influence on the immune system and cognitive functions. Cognitive disorders, including dementia and Parkinson’s disease, represent substantial global health challenges. This review explores the relationship between gut microbiota, immune modulation, and cognitive decline, with a particular focus on the gut-brain axis. Research indicates that gut bacteria produce metabolites, including short-chain fatty acids (SCFAs), which affect mucosal immunity, antigen presentation, and immune responses, thereby influencing cognitive functions. A noteworthy correlation has been identified between imbalances in the gut microbiome and cognitive impairments, suggesting novel pathways for the treatment of cognitive disorders. Additionally, factors such as diet, environment, and pharmaceuticals play a role in shaping the composition of the gut microbiome, subsequently impacting both immune and cognitive health. This article aims to clarify the complex interactions among gut microbiota, immune regulation, and cognitive disorders, evaluating their potential as therapeutic targets. The goal is to promote microbiome-based treatments and lay the groundwork for future research in this field.